2023
DOI: 10.1002/advs.202300032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Histone Lysine Acetoacetylation as a Dynamic Post‐Translational Modification Regulated by HBO1

Abstract: Ketone bodies have long been known as a group of lipid‐derived alternative energy sources during glucose shortages. Nevertheless, the molecular mechanisms underlying their non‐metabolic functions remain largely elusive. This study identified acetoacetate as the precursor for lysine acetoacetylation (Kacac), a previously uncharacterized and evolutionarily conserved histone post‐translational modification. This protein modification is comprehensively validated using chemical and biochemical approaches, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Additionally, simultaneous detection of multiple hPTMs requires multiple membrane washes and successive antibody reincubation steps, making the process very time-consuming. In recent years, a transformative advancement in the form of MS has offered a sensitive and efficient pathway for detecting hPTMs. For example, Dr. Cuomo et al conducted a profiling of 24 distinct hPTMs of histone . In a similar manner, Dr. Leroy et al reported the abundances of single and combinatorial hPTMs among different cancer cell lines, identifying an enrichment of combinatorial hPTMs containing H3K27 methylation in breast cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, simultaneous detection of multiple hPTMs requires multiple membrane washes and successive antibody reincubation steps, making the process very time-consuming. In recent years, a transformative advancement in the form of MS has offered a sensitive and efficient pathway for detecting hPTMs. For example, Dr. Cuomo et al conducted a profiling of 24 distinct hPTMs of histone . In a similar manner, Dr. Leroy et al reported the abundances of single and combinatorial hPTMs among different cancer cell lines, identifying an enrichment of combinatorial hPTMs containing H3K27 methylation in breast cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gao et al utilized several biochemical assays to validate the presence of histone lysine acetoacetylation (Kacac) in humans, mice, and zebrafish and identified 33 Kacac sites on histones. 130 Kacac is regulated via EAA and the ketogenesis pathway. HBO1 is a lysine acetoacetyltransferase through binding acetoacetyl-CoA and key amino acid residues, and HDAC3 is a deacetoacetylase by removing histone acetoacetylation in vitro.…”
Section: Succinylationmentioning
confidence: 99%
“…As another component of ketone bodies, acetoacetate may also serve as a precursor to modify histone lysine, similar to β-hydroxybutyrylation. Recently, Gao et al utilized several biochemical assays to validate the presence of histone lysine acetoacetylation (Kacac) in humans, mice, and zebrafish and identified 33 Kacac sites on histones . Kacac is regulated via EAA and the ketogenesis pathway.…”
Section: Introductionmentioning
confidence: 99%